2014
DOI: 10.1136/injuryprev-2013-041002
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle-related genitourinary injuries in the USA from 2002–2010

Abstract: Among children, the incidence of bicycle-related genitourinary (GU) injuries was 448 per 100 000 (95% CI 383 to 514) and, among adults, was 53 per 100 000 (95% CI 36 to 71). Although children sustained more injuries, adults were more likely to being admitted to the hospital for the GU injury (OR 1.95, 95% CI 1.13 to 3.37). Children sustain nearly 10 times more GU injuries due to bicycles than adults, but adults have higher odds of sustaining injuries requiring admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Most cycling‐related injuries are trauma related, although chronic overuse injuries to ulnar, median, and tibial nerve have also been reported in the literature . Low serum testosterone has been identified in up to 50% of elite aerobic male athletes participating in ultra‐endurance events; however, the association with ED is unknown .…”
Section: Discussionmentioning
confidence: 99%
“…Most cycling‐related injuries are trauma related, although chronic overuse injuries to ulnar, median, and tibial nerve have also been reported in the literature . Low serum testosterone has been identified in up to 50% of elite aerobic male athletes participating in ultra‐endurance events; however, the association with ED is unknown .…”
Section: Discussionmentioning
confidence: 99%
“…Females sustained more overall injuries than did males. However, males sustained proportionally more severe injuries than females, probably related to males engaging in greater risk-taking behaviour than females [11]. All types of injury were most commonly seen between the ages of 5-9 years (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…7 Concerning the genitourinary (GU) tract, it was found that bicycles are the product that is most often associated with GU injuries (>4000 GU injuries in the United States each year), accounting for 13% and 8% of all GU injuries in children and adults, respectively. 8 Besides acute injuries, bicycle overuse injuries can also affect the GU tract. Especially genital numbness and erectile dysfunction (ED) have been reported throughout literature.…”
mentioning
confidence: 99%